GPBAR1 is associated with asynchronous bone metastasis and poor prognosis of hepatocellular carcinoma - Chen, Nan; Wang, Jieqing; Zhou, Lei; Hu, Baiqiang; Chen, Yinzhong; Zhu, Zhuangchen (Frontiers in Oncology, 2023)
Background Hepatocellular carcinoma (HCC) is the second leading cause of cancer-related death in China. Asynchronous metastasis is the main reason for HCC recurrence, but the current assessment of HCC metastasis and prognosis is far from clinically satisfactory. Materials In our study, we investigated the expression of G-protein-coupled bile acid receptor (GPBAR1) in HCC tissues and tumor-adjacent tissues by qRT-PCR and immunohistochemistry. The associations between GPBAR1 expression, clinicopathological factors, and asynchronous metastases were assessed by the Chi-square test. The overall survival curves of different variables were plotted with the Kaplan–Meier method, and the statistical significance between different subgroups was analyzed with the log-rank test. The independent prognostic factors were identified by the Cox regression hazard model. Results GPBAR1 was more highly expressed in HCC tissues than in tumor-adjacent tissues. GPBAR1 expression in HCC was significantly higher than that in liver cirrhosis, followed by normal liver tissues. GPBAR1 was significantly associated with poor prognosis in HCC and can be regarded as an independent prognostic biomarker. Interestingly, GPBAR1 expression in HCC was significantly correlated with asynchronous metastasis to the bone but not to the liver or lung. Conclusions GPBAR1 was found to be an independent, unfavorable prognostic factor of HCC, as well as an indicator of asynchronous bone metastasis but not liver or lung metastases. Our results could provide a new aspect for HCC metastasis studies and help identify high-risk HCC patients, which helps ameliorate the prognostic assessment of HCC.